Solidworks Modeling of Mechanical Strength of an Optimum High Pressure A360 Die Cast - Ubani, N. O.; Dara, J. E.; Ezechukwu, V. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
In this study, SolidWorks modeling was utilized to analyze the mechanical strength of high pressure A360 die castings. The model incorporates all necessary factors, such as material properties and design features, to accurately predict the tensile strength and flexural strength of A360 die cast components. From the input data, a statistical analysis was performed to identify key factors that affect the mechanical strength of the die cast materials. These factors were then used to build a regression model that accurately predicts the mechanical strength of the materials. By simulating various stress and strain scenarios, this research provides an in-depth understanding of the material’s strength and its behavior under different loading conditions. The results showed that the maximum tensile stress of 13.401 MPa was recorded on application of 1000 N tensile load. The maximum elongation associated with 1000 N tensile load was 0.0139 mm. The maximum stresses due to concentrated and distributed 1000 N flexural loads were 66.820 MPa and 43.506 MPa respectively. The maximum deflection of 0.0527 mm was recorded due to concentrated flexural load of 1000 N and the maximum deflection due to distributed flexural loading of 1000 N/mm was 0.0371 mm. The results of this study can be used to optimize the design process of high pressure A360 die cast components, leading to improved performance and increased reliability. This will greatly aid in the design and manufacturing process, allowing for optimized designs and improved product performance. This study serves as a valuable resource for engineers and manufacturers looking to optimize the mechanical strength of their high pressure A360 die castings.